PCSK9: A Potential Therapeutic Target for Sepsis. (15th October 2020) - Yuan, Yuan; Wu, Wei; Sun, Shanshan; Zhang, Yi; Chen, Zhi
Abstract : Sepsis is a life-threatening organ dysfunction syndrome caused by a dysregulated host response to infection. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is often upregulated in the presence of sepsis and infectious diseases. In sepsis, PCSK9 degraded the low-density lipoprotein cholesterol (LDL) receptors (LDL-R) of the hepatocytes and the very low-density lipoprotein cholesterol receptors (VLDL-R) of the adipocytes, which then subsequently reduced pathogenic lipid uptake and clearance/sequestration. Moreover, it might improve cholesterol accumulation and augment toll-like receptor function in macrophages, which supported inflammatory responses. Accordingly, PCSK9 might show detrimental effects on immune host response and survival in sepsis. However, the exact roles of PCSK9 in the pathogenesis of sepsis are still not well defined. In this review, we summarized the literatures focusing on the roles of PCSK9 in sepsis. Our review provided an additional insight in the role of PCSK9 in sepsis, which might serve as a potential target for the treatment of sepsis.